Wnt5a-Mediated Neutrophil Recruitment Has an Obligatory Role in Pressure Overload–Induced Cardiac Dysfunction. Issue 6 (6th August 2019) - Wang, Ying; Sano, Soichi; Oshima, Kosei; Sano, Miho; Watanabe, Yosuke; Katanasaka, Yasufumi; Yura, Yoshimitsu; Jung, Changhee; Anzai, Atsushi; Swirski, Filip K.; Gokce, Noyan; Walsh, Kenneth
Abstract : Background: Although the complex roles of macrophages in myocardial injury are widely appreciated, the function of neutrophils in nonischemic cardiac pathology has received relatively little attention. Methods: To examine the regulation and function of neutrophils in pressure overload–induced cardiac hypertrophy, mice underwent treatment with Ly6G antibody to deplete neutrophils and then were subjected to transverse aortic constriction. Results: Neutrophil depletion diminished transverse aortic constriction–induced hypertrophy and inflammation and preserved cardiac function. Myeloid deficiency of Wnt5a, a noncanonical Wnt, suppressed neutrophil infiltration to the hearts of transverse aortic constriction–treated mice and produced a phenotype that was similar to the neutropenic conditions. Conversely, mice overexpressing Wnt5a in myeloid cells displayed greater hypertrophic growth, inflammation, and cardiac dysfunction. Neutrophil depletion reversed the Wnt5a overexpression–induced cardiac pathology and eliminated differences in cardiac parameters between wild-type and myeloid-specific Wnt5a transgenic mice. Conclusions: These findings reveal that Wnt5a-regulated neutrophil infiltration has a critical role in pressure overload–induced heart failure. Abstract : Supplemental Digital Content is available in the text.